Nucleotide diversity of 15 conifer species in Vietnam’ s central highlands based on the analysis of its, trnH-psbA, matK, trnL and rpoC1 gene regions - Phong, Dinh Thi; Hien, Vu Thi Thu; Lieu, Tran Thi (Vietnam Journal of Science and Technology, 2018)
In this study, five DNA sequences from ITS, trnH-psbA, matK, trnL and rpoC1 gene regions were used to explore relationships of 15 conifer species in Highlands of Vietnam. All target gene segments has been cloned at size as predicted by the theory for all 15 species of conifers. Nucleotide-level change of 15 coniferous species in five gene regions showed from the highest to the lowest as follows: the ITS gene region (0.428), the trnH-psbA region (0.378), the trnL (0.354), the matK gene (0.192) and the rpoC1 gene (0.105). The matK gene region showed the highest level of conservation (671 nucleotides) and the trnH-psbA gene region showed the lowest (78 nucleotides). Phylogenetic tree showed that the species in the same family are formatted in a separate evolutionary branch with bootstrap values ​​obtained from the branching nodes of each species ranging from 52 to 97% for the ITS gene, from 50 to 100% for trnH-psbA gene region, from 66 to 100% for matK gene region, from 50 to 100% for trnL gene region and from 57 to 100% for rpoC1 gene region. Of the three gene regions of matK, trnL and rpoC1, the grouping of species in the same family showed the most obvious. This result suggests the three gene regions of matK, trnL and rpoC1 could be used as barcode for the 15 conifer species in central highlands of Vietnam.